Lateral Heat Transport in the Lofoten Basin: Near-Surface Pathways and Subsurface Exchange - Dugstad, Johannes Sandanger; Fer, Ilker; Lacasce, Joseph Henry; Sanchez de la Lama, Marta; Trodahl, Marta (Journal of Geophysical Research: Oceans, 2020)
The Lofoten Basin in the Nordic Seas plays a central role in the Atlantic overturning circulation by acting as a reservoir for the warm and saline Atlantic Water flow toward the Arctic Ocean. The mass and heat exchange between Atlantic Water and the Lofoten Basin impacts the water mass transformations and the surface heat loss, but the processes governing this exchange are not well understood or quantified. Here we study the circulation in the Nordic Seas and the heat transport in the Lofoten Basin using a combination of Lagrangian and Eulerian methods. We analyze the trajectories of about 150 surface drifters, augmented with a set of about 47,000 surface trajectories calculated using the output from a regional numerical simulation, to investigate the drifter pathways and their exchange with the Lofoten Basin. The drifters reveal that water parcels with long residence time inside the basin contribute substantially to the heat loss and typically enter from south across the outer rim of the Vøring Plateau and, to some extent from east, from the eastern branch of the Norwegian Atlantic Current. The main contributors to the lateral heat transport to the Lofoten Basin are the near‐surface heat transport by the mean flow in the southern sector of the basin and the subsurface eddy fluxes from the Lofoten Escarpment in the east. publishedVersion